Characterization & analysis on electrolytic decomposition of hydroxylammonium nitrate (HAN) ternary mixtures in microreactors - Chai, Wai Siong (2017)
Rapid development of micropropulsion systems arose from growing interest on micro- and nanosatellites. Utilization of liquid energetic materials such as hydrazine and hydrogen peroxide as propellant in propulsion yielded promising results. However, safety issue remains a great concern as hydrazine is highly toxic. This drives the development of propellants towards lower toxicity and more environmental friendly, namely green propellants.